EFEKTIVITAS PENGGUNAAN MEDIA REALIA MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA - Rini Hardiyanti Afifah; Pramudiyanti Pramudiyanti; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2013)
Critical thinking skills (CBC) should be owned by every student. Observations indicate that the CBC eighth grade students of SMP Negeri 19 F Bandar Lampung is not optimal . The purpose of this study was to determine the effectiveness of media realia through cooperative learning model type STAD the critical thinking skills of students in the subject matter of Structure and Function of Plants. The study design was a pretest-posttest non-equivalent. Quantitative data obtained from the value of the pretest, posttest, and N-gain statistically analyzed using t-test with 5% probability level. Qualitative data in the form of student activity data and questionnaire responses realia media students through model type STAD The results showed that the applicability of realia media through type STAD cooperative learning model is effective in improving students' critical thinking skills. In addition, an increase in students in the experimental class KBK with an average gain of 49.41% N-are the criteria being. The average percentage of student learning activities in all aspects of that observed in the experimental class had sufficient criterion is 43.56%. Most of the students gave a positive response to the use of realia media through STAD cooperative learning model type. Thus, through the use of realia media type STAD cooperative learning model is effective in improving students' critical thinking skills.Keywords: Media realia, type STAD cooperative learning, CBC, Structure and Function mainly description